Ideology and the Role of Natural Resources in Bolivia. Issue 3 (3rd July 2019) - Montero Kuscevic, Casto Martín
Abstract: The growth literature has identified four channels of transmission by which the abundance of natural resources can negatively affect economic growth. In this article, I suggest ideology as a fifth transmission channel. To test this hypothesis, I exploit the geography of Bolivia whose western regions have natural resources that differ considerably from its eastern regions. I find that regions with predominantly extractive natural resources tend to choose redistributive and interventionist rather than laissez-faire policies. Additionally, I identify two effects on growth depending upon the type of natural resource that a region possesses in abundance.